The Shared Future Between Open Science and Artificial Intelligence: Spanish translation - da Silveira, Lúcia (2024)
This editorial provides an initial reflection on the relationship between Open Science and Artificial Intelligence (AI), highlighting their interdependencies, barriers, and investment disparities. It advocates global initiatives adapted to local realities to consolidate inclusive advances that respect diversity and sustainability in scientific and technological production.